2021
DOI: 10.1016/j.jad.2020.12.186
|View full text |Cite
|
Sign up to set email alerts
|

The mental health and lifestyle impacts of COVID-19 on bipolar disorder

Abstract: Background It is unclear how those with bipolar disorder (BD) have been affected by the coronavirus (COVID-19) pandemic. This study aimed to obtain a more detailed understanding of the current mental health needs of these individuals, which is important for both the development of intervention strategies to better manage patient distress and to better prepare for similar circumstances in future. Methods The sample comprised 43 individuals with a verified diagnosis of BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 14 publications
2
50
0
1
Order By: Relevance
“…Of these, 440 studies were excluded at the title/abstract level, and an additional 198 records were excluded following full-text review, as detailed in the supplementary material n.2. A total of 14 studies ( Ackerman et al, 2020 , 2021 ; Carmassi et al, 2020 ; Carta et al, 2021 ; Dattoli et al, 2020 ; Karantonis et al, 2021 ; Korten et al, 2021 ; Lazzari et al, 2020 ; McBride et al, 2021 ; Tundo et al, 2021 ; Uvais, 2020 ; Wang et al, 2021 ; Yin et al, 2020 ; Yocum et al, 2021 ) were eligible for inclusion. Please refer to figure 1 (study flow) and table 1 for additional details.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 440 studies were excluded at the title/abstract level, and an additional 198 records were excluded following full-text review, as detailed in the supplementary material n.2. A total of 14 studies ( Ackerman et al, 2020 , 2021 ; Carmassi et al, 2020 ; Carta et al, 2021 ; Dattoli et al, 2020 ; Karantonis et al, 2021 ; Korten et al, 2021 ; Lazzari et al, 2020 ; McBride et al, 2021 ; Tundo et al, 2021 ; Uvais, 2020 ; Wang et al, 2021 ; Yin et al, 2020 ; Yocum et al, 2021 ) were eligible for inclusion. Please refer to figure 1 (study flow) and table 1 for additional details.…”
Section: Resultsmentioning
confidence: 99%
“…Please refer to figure 1 (study flow) and table 1 for additional details. Among the included studies, 6 studies ( Ackerman et al, 2020 ; Carmassi et al, 2020 ; Dattoli et al, 2020 ; Lazzari et al, 2020 ; Uvais, 2020 ; Yin et al, 2020 ) were published in 2020, and 8 studies ( Ackerman et al, 2021 ; Carta et al, 2021 ; Karantonis et al, 2021 ; Korten et al, 2021 ; McBride et al, 2021 ; Tundo et al, 2021 ; Wang et al, 2021 ; Yocum et al, 2021 ) were published in the year 2021. A total of 6 studies ( Carmassi et al, 2020 ; Dattoli et al, 2020 ; Korten et al, 2021 ; Lazzari et al, 2020 ; McBride et al, 2021 ; Tundo et al, 2021 ) were conducted in Europe, 4 studies ( Ackerman et al, 2020 , 2021 ; Wang et al, 2021 ; Yocum et al, 2021 ) in North America, 2 studies ( Uvais, 2020 ; Yin et al, 2020 ) in Asia, one study ( Karantonis et al, 2021 ) in Oceania, and one study included two different samples from independent geographical regions (Europe and Africa) ( Carta et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these factors are not specific for anxiety and depressive disorders and are expected to decrease visit rates for all diagnoses. Studies have reported no significant change regarding the visit rates bipolar disorder patients during the pandemic [ 35 , 36 ]. Possible explanations of these contradictory findings on anxiety, depression, and bipolar disorders are the relatively small sample size and different methodology of these studies, as well as cultural differences of the countries that affect psychological reactions of the populations.…”
Section: Discussionmentioning
confidence: 99%